Calcium imaging: A versatile tool to examine Huntington’s disease mechanisms and progression - Barry, Joshua; Peng, Allison; Levine, Michael S.; Cepeda, Carlos (Frontiers in Neuroscience, 2022)
Huntington’s disease (HD) is a fatal, hereditary neurodegenerative disorder that causes chorea, cognitive deficits, and psychiatric symptoms. It is characterized by accumulation of mutant Htt protein, which primarily impacts striatal medium-sized spiny neurons (MSNs), as well as cortical pyramidal neurons (CPNs), causing synapse loss and eventually cell death. Perturbed Ca2+ homeostasis is believed to play a major role in HD, as altered Ca2+ homeostasis often precedes striatal dysfunction and manifestation of HD symptoms. In addition, dysregulation of Ca2+ can cause morphological and functional changes in MSNs and CPNs. Therefore, Ca2+ imaging techniques have the potential of visualizing changes in Ca2+ dynamics and neuronal activity in HD animal models. This minireview focuses on studies using diverse Ca2+ imaging techniques, including two-photon microscopy, fiber photometry, and miniscopes, in combination of Ca2+ indicators to monitor activity of neurons in HD models as the disease progresses. We then discuss the future applications of Ca2+ imaging to visualize disease mechanisms and alterations associated with HD, as well as some of our own studies showing how, as a proof-of-concept, Ca2+imaging using miniscopes in freely-behaving animals can help elucidate the differential role of direct and indirect pathway MSNs in HD symptoms.